2008
DOI: 10.1152/ajpregu.90352.2008
|View full text |Cite
|
Sign up to set email alerts
|

Central infusion of aldosterone synthase inhibitor prevents sympathetic hyperactivity and hypertension by central Na+ in Wistar rats

Abstract: In Wistar rats, increasing cerebrospinal fluid (CSF) Na+ concentration ([Na+]) by intracerebroventricular (ICV) infusion of hypertonic saline causes sympathetic hyperactivity and hypertension that can be prevented by blockade of brain mineralocorticoid receptors (MR). To assess the role of aldosterone produced locally in the brain in the activation of MR in the central nervous system (CNS), Wistar rats were infused ICV with artificial CSF (aCSF), Na+ -rich (800 mmol/l) aCSF, aCSF plus the aldosterone synthase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 28 publications
2
53
0
Order By: Relevance
“…In a previous study, Connell et al 1 showed that the central nervous system can produce aldosterone. Furthermore, using FAD286, Gomez-Sanchez et al 2 and Hung et al 6,7 proved that aldosterone is synthesized in the brain. Kumar et al 4 demonstrated the presence of aldosterone-related mRNA species in the RVLM.…”
Section: Effect Of Fad286 On Bulbospinal Neurons In the Rvlmmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Connell et al 1 showed that the central nervous system can produce aldosterone. Furthermore, using FAD286, Gomez-Sanchez et al 2 and Hung et al 6,7 proved that aldosterone is synthesized in the brain. Kumar et al 4 demonstrated the presence of aldosterone-related mRNA species in the RVLM.…”
Section: Effect Of Fad286 On Bulbospinal Neurons In the Rvlmmentioning
confidence: 99%
“…5,6 Recent studies have demonstrated the existence of an aldosterone system in the brain, 4 and an increase in [Na þ ] in cerebrospinal fluid (CSF) has been shown to increase aldosterone biosynthesis. 7 Although the mechanism was unknown, Zhang et al 3 demonstrated that aldosterone upregulated key elements (angiotensin II type 1 receptor and angiotensin-converting enzyme in the brain reninangiotensin system) and induced oxidative stress in the hypothalamus. They suggested that aldosterone increased sympathetic nerve activity through those mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The sympathoexcitatory and hypertensive responses to intracerebroventricular infusion of Na ϩ -rich aCSF or ouabain can also be inhibited by intracerebroventricular losartan (13). Altogether, these results suggest that in response to a chronic increase in CSF [Na ϩ ], increased binding of an endogenous agonist (presumably aldosterone) (15) to MRs mediates the activation of benzamil-blockable Na ϩ influx, leading to "ouabain" release and ANG II type 1 (AT 1 ) receptor stimulation. Where and how in the CNS these mechanisms interact have not yet been studied.…”
mentioning
confidence: 92%
“…For example, both acute and chronic peripheral aldosterone administration impaired baroreceptor responses in dogs (6) and in humans (7). In addition, central infusion of sodium-enriched artificial cerebrospinal fluid (aCSF) caused increased aldosterone and corticosterone levels in the hypothalamus and impaired baroreceptor function (8,9), suggesting a role for central aldosterone in baroreflex function. However, the role of aldosteronesensitive neurons in the NTS in baroreflex responses remains unclear.…”
mentioning
confidence: 99%
“…In fact, central infusion of sodium-rich artificial CSF increased aldosterone content in the hypothalamus, suggesting that high sodium levels may cause region-specific aldosterone synthesis (8,9). Increased sodium can also cause impairment of the baroreflex function (8,9).…”
mentioning
confidence: 99%